1996
DOI: 10.1111/j.1365-2621.1996.tb14714.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Oxidation Potential of Beef, Chicken, and Pork

Abstract: Beef and pork longissimus dorsi and semimembranosus muscles and chicken breast and thigh muscles were excised 24 hr postmortem from carcasses of marketweight grain-finished feedlot beef cattle, marketweight hogs on a typical finishing diet, and broilers on a commercial grain diet. Muscle samples were immediately ground and formed into patties and stored raw or after cooking, at 4ЊC (cooked) or Ϫ20ЊC (raw and cooked). TBA values (on sample weight basis) of frozen raw samples were higher for beef and pork than f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
101
3
12

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(139 citation statements)
references
References 34 publications
17
101
3
12
Order By: Relevance
“…Production of antioxidants in beef itself at high sterilization temperature was responsible for the stability against oxidative rancidity (Zipser and Watts 1961). TBARS value of raw and cooked muscles of beef, chicken and pork had increased during storage (Rhee et al 1996).…”
Section: Quality Changes During Storagementioning
confidence: 99%
“…Production of antioxidants in beef itself at high sterilization temperature was responsible for the stability against oxidative rancidity (Zipser and Watts 1961). TBARS value of raw and cooked muscles of beef, chicken and pork had increased during storage (Rhee et al 1996).…”
Section: Quality Changes During Storagementioning
confidence: 99%
“…The higher TBARS values for beef samples as compared to chicken samples may also be partly due to the lower pH values of beef. Note that the fat in chicken breast meat is usually much more polyunsaturated than the fat from beef muscles or separable lean (Rhee et al 1996). Hernandez et al (2002) indicated that ionic strength increase can affect the stability of antioxidant enzymes, with GSH-Px being affected more than catalase.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanatory factor was the difference in the phospholipids, polyunsaturated fatty acids (PUFA) and/or free iron contents between the two meat species (Rhee et al, 1996). Ferric and ferrous irons catalyze the decomposition of lipid peroxides to more volatile aldehydes and ketones (Baron and Andersen, 2002).…”
Section: Thiobarbituric Acid Reactive Substances (Tbars) Analysismentioning
confidence: 99%
“…Meat is recognized as one of the most perishable foods, and consumers prefer meats that are high in polyunsaturated fatty acids (PUFAs) and myoglobin, for its high ferrous iron and phospholipid content (Enser et al, 1996;Rhee et al, 1996). Some researchers have reported that crude clove extracts have the greatest total phenolic contents and ferricreducing antioxidant power out of 32 tested spices, are also strongly inhibitory of TBARS formation (Wojdyło et al, 2007), and thereby improved the quality and nutritional value of cooked pork patties (Kong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation